Provision of Elimination of Tax Administrative Sanctions in Indonesia on 2008 and 2015 Case: Establishment of Tax Law - Anggia, Putri (Faculty of Law, Universitas Negeri Semarang, 2016)
Elimination of administrative sanctions or Sunset Policy on 2008 intended to achieve the target of tax revenue and to strengthen the data base by providing incentives in the form of taxation, was not done due diligence measures. Removal of administrative sanctions in 2015 was motivated by the goal of achieving the target of tax revenue and more specific purpose, namely as a continuation next year, the year of law enforcement. Removal of Administrative Sanction was not in accordance with the theory of devotion. Implementation of the elimination of administrative sanction give leeway to the taxpayer to foster a sense of obligation to pay taxes, so it tends to keep the runway taxation in the theory of filial piety.